Interaction Devices as Assistive Technology: Current Practices about Evaluation Methodologies. Issue 3 (7th February 2022) - Rodrigues, Andreia; Machado, Marcelo Bender; Almeida, Ana Margarida Pisco; Abreu, J. F. D.; Tavares, Tatiana Aires
ABSTRACT: A significant challenge on Assistive Technology (AT) relies on the interaction devices' evaluation phase. Generally, the gap between users and devices is revealed during the use. This fact highlights the relevance of discussing these barriers early in the design process, mainly, in the evaluation phase. This article explores current practices of evaluation methodologies for AT interaction devices, both considering the usage of computers and TV-sets. Two research stages were performed to achieve this objective: a systematic mapping study of AT evaluation methodologies, and field research in Portugal, with experts in AT Evaluation and end-users. This last step was done through semi-structured interviews, whose results passed by a content analysis process. The findings from these researches suggest that there are vital dimensions that should be addressed when evaluating AT. Firstly, qualification issues remain most important, especially concerning to the developers' awareness of end-user needs as, for example, difficulty in computer access. Other important points are the economic problems, involved in the acquisition of AT interaction devices, and the emotional issues related to using these devices. Finally, the article concludes with a discussion on directions for evaluation methodologies of AT interaction devices.